2023
DOI: 10.1371/journal.pntd.0011161
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics, clinical symptoms, biochemical markers and probability of occurrence of severe dengue: A multicenter hospital-based study in Bangladesh

Abstract: Establishing reliable early warning models for severe dengue cases is a high priority to facilitate triage in dengue-endemic areas and optimal use of limited resources. However, few studies have identified the complex interactive relationship between potential risk factors and severe dengue. This research aimed to assess the potential risk factors and detect their high-order combinative effects on severe dengue. A structured questionnaire was used to collect detailed dengue outbreak data from eight representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Moreover, in this work, for generating spatial Maps, publicly available data on dengue cases were obtained from the Directorate GGeneral of Health Services, Bangladesh [ 10 ] and secondary data on dengue cases from outside of Dhaka without travel history (this study was ethically approved by Biomedical Research Foundation, Bangladesh) [ 11 ] and mosquito-related data (this study was ethically approved by icddr,b Bangladesh) [ 12 ] were collected from previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in this work, for generating spatial Maps, publicly available data on dengue cases were obtained from the Directorate GGeneral of Health Services, Bangladesh [ 10 ] and secondary data on dengue cases from outside of Dhaka without travel history (this study was ethically approved by Biomedical Research Foundation, Bangladesh) [ 11 ] and mosquito-related data (this study was ethically approved by icddr,b Bangladesh) [ 12 ] were collected from previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have used AI techniques to explore dengue, performing prediction processes [ 17 ], disease classification [ 18 ], outbreak control [ 19 ], and risk factor verification [ 20 ]. Some studies report the use of AI techniques to predict the development of dengue severity using genetic data.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Hoyos et al [ 24 ] combined artificial neural networks and support vector machines to classify the patient based on dengue severity, achieving 98% accuracy. Yang et al [ 20 ] developed a classification model to find key risk factors in severe dengue cases; the results showed that the probability of the occurrence of severe dengue cases ranged from 7% (age > 12.5 years, without plasma leakage) to 92.9% (age ≤ 12.5 years, with dyspnea and plasma leakage). Chowdhury et al [ 25 ] used the XGBoost classifier with a Shapley dependency plot, finding that low platelet count and elevated hematocrit concentration have greater influences on whether the patient will suffer dengue shock.…”
Section: Related Workmentioning
confidence: 99%
“…La identificación temprana del dengue grave podría ser beneficiosos para que los médicos clínicos tomen oportunamente las medidas pertinentes y disminuir o anular el mayor riesgo de muerte de los casos graves que no se manejan adecuadamente; los factores más importantes para predecir el dengue grave son: la edad, seguido de la educación, la fuga de plasma, las plaquetas y la disnea. Por lo tanto, encontrar biomarcadores que puedan predecir de manera confiable el desarrollo de dengue grave en individuos sintomáticos es uno de los principales enfoques de los esfuerzos de investigación actuales (YANG et al, 2023). (Butantan-DV) (ORELLANO et al, 2016;ORELLANO et al, 2023;ESPAÑA et al, 2021).…”
Section: Podemos Predecir El Degue Grave?unclassified